The handbook of discourse analysis - Tannen, Deborah; Hamilton, Heidi E.; Schiffrin, Deborah (Chichester, West Sussex John Wiley & Sons, Inc., 2018)
"The second edition of the highly successful Handbook of Discourse Analysis has been expanded and thoroughly updated to reflect the very latest research to have developed since the original publication, including new theoretical paradigms and discourse-analytic models, in an authoritative two-volume set."--Provided by publisher.
This edition first published 2015.
Includes bibliographical references and index.
Keywords: Discourse analysis -- Handbooks, manuals, etc